Genetic characterization of the first detected human case of low pathogenic avian influenza A/H9N2 in sub-Saharan Africa, Senegal. Issue 1 (1st January 2020) - Jallow, Mamadou Malado; Fall, Amary; Barry, Mamadou Aliou; Diop, Boly; Sy, Sara; Goudiaby, Déborah; Fall, Malick; Enouf, Vincent; Niang, Mbayame Ndiaye; Dia, Ndongo
ABSTRACT: The H9N2 influenza virus has become one of the dominant subtypes of influenza virus circulating in poultry, wild birds, and can occasionally cross the mammalian species barrier. Here, we report the first human A/H9N2 in Sub-Saharan Africa. The patient was a child of 16 months' old living in the South-West of Senegal. He had no influenza vaccination history and no other disease history. He had symptoms of fever with an auxiliary temperature of 39.1°C. Respiratory symptoms were an intense cough, runny nose and pulmonary crackles. All eight genome segments belonged to the A/H9N2 AIV subtype and the strain characyerized as of low pathogenicity with a RSSR/GLF amino acids motif. Phylogenetic analysis of both complete HA and NA gene segments showed that the A/H9N2 subtype virus from Senegal belonged to the G1 lineage. This human case highlights the weakness of influenza surveillance in animals and the need for enhanced surveillance using a one-health approach.